2017
DOI: 10.7205/milmed-d-16-00054
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Clinical Assessment for Traumatic Brain Injury and Comorbid Post-Traumatic Stress Disorder: A Retrospective Analysis of Virtual Environment Tasks in the Computer-Assisted Rehabilitation Environment

Abstract: The objective of this study was to determine whether physical performance during virtual environment (VE) tasks in the Computer-Assisted Rehabilitation Environment (CAREN) could differentiate between service members (SMs) with a history of traumatic brain injury (TBI) with and without comorbid post-traumatic stress disorder (PTSD). Data were obtained by independent review of clinical notes, objective outcomes, and validated questionnaires from 214 SMs (208 males) with a history of TBI assessed in the CAREN fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…They were outfitted with a full body harness and tethered to the system's safety stand. Once secured, they were taken through a series of preliminary VE tasks specifically developed to acclimate to the CAREN (Onakomaiya et al, 2017). These included the balance balls, balance cubes, and continuous road VEs.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…They were outfitted with a full body harness and tethered to the system's safety stand. Once secured, they were taken through a series of preliminary VE tasks specifically developed to acclimate to the CAREN (Onakomaiya et al, 2017). These included the balance balls, balance cubes, and continuous road VEs.…”
Section: Protocolmentioning
confidence: 99%
“…These VEs allowed participants to become comfortable moving in the harness. The continuous road VE was completed to acclimate participants to flat walking on the system's treadmill; the platform remained flat, and the treadmill speed was synced to a visual representation of a road on the screen to maintain congruence and optical flow (Onakomaiya et al, 2017). The visual display for this VE is shown in Panel A of Figure 1.…”
Section: Protocolmentioning
confidence: 99%
“…Twenty-two articles used the computer-assisted rehabilitation environment system for biomechanical analysis , 15 articles used the computerassisted rehabilitation environment system for rehabilitation [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 4 articles were reviews [19,20,58,59] and 9 articles addressed the computerassisted rehabilitation environment system in other ways [60][61][62][63][64][65][66][67][68]. A flow chart summarizing study selection is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…To acclimate to walking on the CAREN system, service members completed the CAREN Continuous Road (CR) virtual environment 44. The treadmill speed was synced to the optical flow of the virtual path to maintain congruence and increase immersion.…”
Section: Methodsmentioning
confidence: 99%